PWE-058 Co-designing inflammatory bowel disease (ibd) services in scotland: the patients perspective. (22nd June 2015) - Schoultz, M; Macaden, L; Watson, A
Abstract : Introduction: The Scottish Government–s ambition is to ensure that health services are co-designed with the communities they serve. IBD lifelong management has historically been dependent on the available health services. Crohn's and Colitis UK and the Scottish Government have recognised the need to review and update the current IBD care model to a model that reflects the range of daily needs for IBD patients. An online survey was conducted where IBD patients were asked to express their views on what is good about the NHS care they receive, what should improve and anything else they would like to add about living with IBD. This survey is the first step of co-designing and developing a national strategy for IBD service improvement in Scotland. Aim: To explore IBD patients' experiences of current services and make recommendation for future service development. Method: This study was part of a wider on line survey. The online survey was opened between March and May 2014. Participants were IBD patients across Scotland. 777 took part in the survey and 279 participants responded to the open ended questions about their experiences with IBD services. Thematic analysis of all data was conducted independently by two researchers and then grouped under the key themes. Results: Three key themes emerged from the analysis: 1. Quality of life: IBD patients highlighted the huge impact the disease has on quality of life and the desperate and urgent need for better addressing this in a holistic way. 2. IBD clinicians: IBD patients recognise the need for more IBD nurses and gastroenterologists along with better access to them. Those with a named IBD nurse reported to be more satisfied with their care. 3. Clear IBD care pathway: IBD patients identified that better coordination of care and communication between all departments involved in IBD care delivery is needed along with making the IBD care pathway more explicit to IBD patients. Conclusion: IBD patients recognise that while living with IBD, their needs are wider than medical and biological; therefore a more holistic approach to their care is needed. While IBD patents with named IBD nurse reported higher satisfaction with their care, they recognise the need for integrating psychological, counselling and dietician services in the IBD care, together with practical advice on how to live with IBD as soon as diagnosed. Disclosure of interest: None Declared.